2014
DOI: 10.3892/mmr.2014.2089
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gender differences on the regulation of renal ischemia-reperfusion-induced inflammation in mice

Abstract: Inflammation is a key mediator of renal ischemia-reperfusion (IR) injury. Gender disparities have been reported in acute and chronic kidney disease. In particular, males are considered to be more susceptible to renal ischemic injury compared with females according to animal studies. The purpose of the present study was to investigate the effect of gender on the renal inflammatory response following acute renal IR injury in mice. Experiments were performed in male and female C57BL/6 mice. Two weeks prior to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
109
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 16 publications
10
109
0
Order By: Relevance
“…Finally, according to previous research, male are more sensitive to renal I/R injury than female (35), however, no difference in gender was observed in our model when L-arg or EX were administrated against kidney I/R injury.…”
Section: Discussionsupporting
confidence: 71%
“…Finally, according to previous research, male are more sensitive to renal I/R injury than female (35), however, no difference in gender was observed in our model when L-arg or EX were administrated against kidney I/R injury.…”
Section: Discussionsupporting
confidence: 71%
“…However, more research is needed in this area with the use of safer and more selective agonists than nicotine. In addition, studies need to be performed across species, age, and sex to ensure consistent results and to account for the sex differences noted in both preclinical (Kang et al, 2014) as well as clinical studies demonstrating that sex plays a role in the prediction of renal decline (Halbesma et al, 2008). From preclinical studies, the sex difference Therapeutic Potential of a7 nAChRs resulted in greater renovascular vasodilation in female rat kidney tissue with the suggestion that it could be facilitated by estrogen having a direct effect on a7 nAChR downstream signaling (El-Mas et al, 2011).…”
Section: The Role Of A7 Nicotinic Acetylcholine Receptors In Renalmentioning
confidence: 99%
“…Sexual disparities in response to acute and chronic renal disease have been identified for many years. Animal studies have demonstrated that males are more susceptible to renal injury compared to females [66], and females have a significantly higher ratio of survival when exposed to profound renal ischemia [67]. In the United States (as of 2014), chronic kidney disease is known to affect approximately 30 million adults, where males exhibit a higher prevalence and progression of renal disease, and is associated with a higher incidence of End Stage Renal Disease (ESRD) [68].…”
Section: Discussionmentioning
confidence: 99%